Chemotherapeutic Nanoparticle-Based Liposomes Enhance the Efficiency of Mild Microwave Ablation in Hepatocellular Carcinoma Therapy - Wu, Songsong; Zhang, Dongyun; Yu, Jie; Dou, Jianping; Li, Xin; Mu, Mengjuan; Liang, Ping (Frontiers in Pharmacology, 2020)
Hepatocellular carcinoma (HCC) occupies the third leading cause of cancer death. While the 5-year overall survival (OS) for HCC remains unsatisfying worldwide. Microwave ablation (MWA) as one of minimally invasive therapies has obtained much progress for HCC therapy. However the recurrence is still the main challenge. Combination therapy may offer better outcomes and enhance MWA efficiency with an improved tumor control. Here we developed doxorubicin-loaded liposomes (DNPs) as an efficient nanoplatform to enhance microwave ablation (MWA) of hepatocellular carcinoma even at the mild ablation condition. In this study, we demonstrated that uptake of DNPs by HCC cells was increased 1.5-fold compared with that of free DOX. Enhanced synergism was observed with the combination of DNPs and MWA, which induced nearly 80% cell death. The combination of mild MWA and DNPs enhanced the ablation efficiency of HCC with significant inhibition of liver tumors and produced the longest survival among all groups. A much higher accumulation of the DNPs was observed in the transitional zone than in the ablation zone. No apparent systemic toxicity was observed for any of the treatments at 14 days. Present work clearly showed DNPs combined with MWA could be a promising nanoparticle-based therapeutic approach for the treatment of hepatocellular carcinoma with potential for future clinical applications.